The Holiness-Pentecostal tradition Charismatic movements in the twentieth century - Synan, Vinson (Grand Rapids, MI Eerdmans, 1997)
Includes bibliographical references and index.
First edition published 1971, " Holiness-Pentecostal movement in the United States".
Keywords: Pentecostalism -- History -- 20th century -- United States; Holiness churches -- History -- 20th century -- United States